Environmental economics : - Field, Barry C (McGraw-Hill/Irwin, 2002)
This book introduces environmental economics. It discusses the way human decisions affect the quality of the environment, how human values and institutions shape our demands for improvement in the quality of that environment na dhow to design effective public policies to bring about these improvements